Metagenomic Analysis of Ammonia-Oxidizing Archaea Affiliated with the Soil Group - Bartossek, Rita; Spang, Anja; Weidler, Gerhard; Lanzen, Anders; Schleper, Christa (Frontiers in Microbiology, 2012)
Ammonia-oxidising archaea (AOA) have recently been recognized as a significant component of many microbial communities and represent one of the most abundant prokaryotic groups in the biosphere. However, only few AOA have been successfully cultivated so far and information on the physiology and genomic content remains scarce. We have performed a metagenomic analysis to extend the knowledge of the AOA affiliated with groupI.1b that is widespread in terrestrial habitats and of which no genome sequences has been described yet. A fosmid library was generated from samples of a radioactive thermal cave (46°C) in the Austrian Central Alps in which AOA had been found as a major part of the microbial community. Out of sixteen fosmids that possessed either an amoA or 16S rRNA gene affiliating with AOA, five were fully sequenced, four of which grouped with the soil/I.1b (Nitrososphaera-) lineage and one with marine/I.1a (Nitrosopumilus-) lineage. Phylogenetic analyses of amoBC and an associated conserved gene were congruent with earlier analyses based on amoA and 16S rRNA genes and supported the separation of the soil and marine group. Several putative genes that did not have homologues in currently available marine thaumarchaeota genomes indicated that AOA of the soil group contain specific genes that are distinct from their marine relatives. Potential cis-regulatory elements around conserved promoter motifs found upstream of the amo genes in sequenced (meta-) genomes differed in marine and soil group AOA. On one fosmid, a group of genes including amoA and amoB were flanked by identical transposable insertion sequences, indicating that amoAB could potentially be co-mobilized in the form of a composite transposon. This might be one of the mechanisms that caused the greater variation in gene order compared to genomes in the marine counterparts. Our findings highlight the genetic diversity within the two major and widespread lineages of thaumarchaeota.